Faculty of Pharmacy virtual online Postgraduate Engagement Day 2023 / Dr. Mashani Mohamad and Dr. Gurmeet Kaur Surindar Singh - Mohamad, Mashani; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy organised a Virtual Online Postgraduate Engagement Day Programme, which was successfully conducted on August 17th, 2023, utilising the platforms of WEBEX and YouTube live. The event, led by Dr. Mashani Mohamad, aimed to provide prospective local and international postgraduate students with valuable insights into various programmes and research opportunities at the faculty. This is in parallel with the UiTM vision of emphasising research towards becoming a globally renowned university (GRU). The event commenced with a warm welcome address by Professor Dr. Kalavathy Ramasamy, the Deputy Dean of Research and Innovation, Faculty of Pharmacy, UiTM Puncak Alam, who introduced the faculty’s mission and commitment to academic excellence. Subsequently, Associate Professor Dr. Meor Mohd Redzuan Meor Mohd Affandi, the Head of Postgraduate Programme, delivered a presentation encompassing the array of programmes offered, the structure of these programmes, the admission procedure, and success stories. The event also included presentations by the heads and representatives of the Pharmaceutical Life Sciences, Pharmacology and Pharmaceutical Chemistry, Pharmacy Practice, and Pharmaceutics departments. The purpose of these presentations was to introduce the research themes and potential supervisors to the attendees. To enthuse and motivate prospective students, Mr. Yazid Zaki, the president of the Pharmacy Postgraduate Society, offered a captivating overview of the dynamic academic and social dimensions of postgraduate life at our esteemed faculty. The organisers also curated a selection of videos, featuring immersive glimpses into our cutting-edge research centres, virtual faculty tours, state-of-the-art facilities, laboratories, and abundant resources accessible to postgraduate students.